Diagnostic spectrum of unplanned acute hospital admissions within 30 days after emergency department presentation for vertigo in older adults: a province-wide retrospective cohort study - İskender Aksoy; Mehmet Ekiz (Frontiers in Medicine, 2026)
Background Vertigo is a common reason for emergency department (ED) attendance and is frequently evaluated with a primary focus on excluding stroke. However, the broader spectrum of serious diagnoses following vertigo presentation in older adults remains insufficiently characterized. We aimed to characterize 30-day hospital admissions among patients aged 65 years and older presenting to the ED with vertigo, with particular attention to diagnoses beyond stroke. Methods This province-wide retrospective cohort study included patients aged ≥65 years presenting to 17 EDs in Giresun, Türkiye, with vertigo-related ICD-10 codes between January 2024 and December 2025. ICD-10 coding was used as an initial case-finding strategy, and only patients in whom vertigo was confirmed as the dominant presenting complaint after clinical record review were included in the final analysis. Patients were categorized according to admission timing; clinical characteristics, imaging use, risk scores, and final diagnoses were summarized descriptively, with exploratory between-group comparisons. Results Among 6,460 older adults identified through vertigo-related ICD-10 codes, 269 had an unplanned acute hospital admission through an ED within 30 days after the index visit. After clinical record review, 186 patients with vertigo as the dominant presenting complaint were included in the final analysis. The mean age of the study cohort was 75.9 ± 7.2 years, and 106 patients (57.0%) were male. Seventy patients (37.6%) were admitted during the index ED visit, whereas 116 (62.4%) were admitted after ED discharge. Neurological emergencies accounted for 84 admissions (45.2%), of which 74 (39.8% of the total cohort) were strokes. Among the 116 admissions occurring after ED discharge, 79 (68.1%) were attributable to diagnoses other than stroke, including 71 (61.2%) due to non-neurological conditions, most commonly metabolic/renal, infectious, and cardiac disorders. Conclusion Among older adults admitted within 30 days after an ED presentation with vertigo, non-neurological diagnoses constituted a substantial proportion of hospitalizations after ED discharge. These findings describe the diagnostic spectrum of a hospitalization-conditioned cohort and should not be interpreted as estimates of overall admission risk or diagnostic accuracy.